Peculiarities of Grammatical Properties in Nominal Word Combinations - Klienkova, I. B. (Vestnik MGIMO-Universiteta, 2014)
The article examines some peculiarities if grammatical properties of nominal word combinations based on the study of German-speaking Swiss press. The accumulated experience of linguists is analyzed and certain factors influencing the choice of syntactic relations in nominal word combinations with quantitative meaning are researched. It has been established that the choice of syntactic relations in such word combinations is determined by functional style, semantics and grammatical features of nouns - first or second components in a word combination. The aforementioned factors influencing the choice of syntactic relations in quantitative nominal word combinations are studied on the material of Germanspeaking Swiss press. The research revealed a number of peculiarities. First of all, German-speaking Swiss press uses such syntactic relation as genitive subordination quite often, not only on "special occasion" and unlike its use in Germany does not produce a magniloquent, pompous impression. Secondly, it has been established that the choice of syntactic relations in word combinations of the above-mentioned type of word combinations greatly depends on the semantic meaning of the noun - the first component of the word combination - and does not always coincide with the grammatical properties in nominal combinations in Germany. Thirdly, a clear dependence of syntactic relations choice is observed. Moreover, the article highlights the importance of grammatical features of the second component. These are such features as gender, number, case accompanied by noun declension. All the afore-mentioned features help to define the type of syntactic relations, which nominal quantitative word combinations may be connected by. The results of the comparisons of grammatical properties of quantitative nominal word combinations in German and Swiss press are demonstrated in a table below.